HUBUNGAN EFIKASI DIRI, RESILIENSI, DAN KEBERMAKNAAN HIDUP PADA GURU HONORER DI KEMENTERIAN AGAMA KABUPATEN POLEWALI MANDAR - Sudirman Sudirman; Saifuddin Saifuddin (JPPI (Jurnal Pendidikan Islam Pendekatan Interdisipliner), 2020)
The meaning of life is an considered important because it is associated with the creation of sense and happiness. The aim of the research to penar the relationship of self-efficacy, resilience to the meaningful of life. The research involved 50 part time teachers at the school of the Ministry of Religious Polewali Mandar. The research collecting the data using Self Efficacy Scale (SES), Resilience Scale (RS), and the Meaning of Life Questionnaire (MLQ). Analysis of data using multiple regression. The results of correlation analysis obtained positive relationship between self-efficacy with the meaningfulness of life (r = 0.516, p <= 0.1), and positive correlation resilience and the meaning of life (r = 0.574, p <= 0.1). In the regression analysis results that self efficacy and resilience effected the meaning of life (F=18,008, p=0,000, R²=0,434). This value indicates that self efficacy and resilience contribute 43.4% to the meaning of life. Based on the results of the analysis of this hypothesis can be accepted that there is a positive and significant between self-efficacy and resilience with the meaning of life, with the effective contribution of each predictor. Self-efficacy had a contribution of 18.0% and resiliency had a contribution of 25%.